All flesh is grass : the pleasures and promises of pasture farming - Logsdon, Gene (Swallow Press, 2004)
"Amid Mad Cow scares and consumer concerns about how farm animals are bred, fed, and raised, many farmers, homesteaders, and consumers are rediscovering the benefits of pastoral agriculture. In All Flesh Is Grass: The Pleasures and Promises of Pasture Farming, Logsdon explains that well-managed pastures are nutritious and palatable - virtual salads for livestock. Leafy pastures also hold the soil, increase biodiversity, and create lovely landscapes." "Logsdon explains historically effective grazing practices and new techniques that have blossomed during the past decade. His narrative is enriched by profiles of successful grass farmers and by his experience as a "contrary farmer" on his own artisan-scale farm."--BOOK JACKET